ELIZABETH BISHOP’S ONE ART: PHONOLOGICAL ANALYSIS - GIDO, NATHANIEL G.; S. CASIÑO, MICHAEL VINCENT; HALINA, KISHA L. (International Journal of Multidisciplinary Research and Studies, 2022)
Elizabeth Bishop Poem's One Art is utilizing textual analysis employing phonological analysis. The poem reveals rhyming sounds that are evident in poem like alliteration and assonance. It is argued that Bishop's poetry achieves real power just by being honest. In order to connect with her audience and write a poem about a subject that many people, especially women, care about, the poet, a woman draws on her own life experiences. She touches on a sensitive subject for many women when she mentions losing a gold watch or forgetting names: the dread of losing something dear to them, like their mother's watch, or of becoming older and forgetting things or experiencing memory issues. It's important to keep in mind that the poet's own experiences and viewpoints influence the poetry and aid in making the audience believe it. The reader will see a comparison of losses between several items in this poetry. The poet employed rich structural and sardonic structure to create a very straightforward but deep poem. She rejects the statement "Loss is not difficult to maser," so you can tell. The final line's shift to "Loss is not so difficult to learn" may be a sign that the poet is finding it harder and harder to cope with the loss of his loved one. Bishop demonstrates how embracing loss and losing the little things enhances the ironic nature of poetry. She is, after all, a tiny "one art." She thinks she can start a new life and progress if she can get out of pain and let go of her emotions, but she finds that to be too challenging. Bishop turns losing into an art form and investigates how, if we can master it, we may become detached from the hurt of loss. Elizabeth Bishop's father passed away when she was just eight months old, her mother later died of a mental condition, and she eventually lost her lover to suicide. We could therefore consider this poem to be partially autobiographical. In it, the poet lists a number of things we might lose in life in order of increasing importance, with the loss of a loved one serving as the list's ultimate resolution.